1999
DOI: 10.3923/pjbs.1999.1366.1370
|View full text |Cite
|
Sign up to set email alerts
|

Variability For Grain Yield, its Components and Quality Traits in a Sweet Corn Population

Abstract: One hundred S 1 families were developed from an open pollinated population of sweet corn. The estimates of genetic variance and broad-sense heritability were significant for all the yield and quality traits. The maximum estimate of broad-sense heritability was for number of grain rows per cob (h 2 = 0.84). Significant and positive estimates of genetic correlations were noted for cob length in combination with number of grains per row (r = 0.75). Similarly, among quality traits, sweetness and sweet flavour show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Results in the literature on heritabilities of yield traits and selection gain in sweet corn are contradictory: Grain yield in sweet corn showed low heritabilities in Asgh's study (Jawad Asgh & Sadaqat Me, 1999). But in contrast, Ojo et al (2020) found high heritabilities for grain yield for 106 full‐sib families (h 2 = .88/.98.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Results in the literature on heritabilities of yield traits and selection gain in sweet corn are contradictory: Grain yield in sweet corn showed low heritabilities in Asgh's study (Jawad Asgh & Sadaqat Me, 1999). But in contrast, Ojo et al (2020) found high heritabilities for grain yield for 106 full‐sib families (h 2 = .88/.98.…”
Section: Discussionmentioning
confidence: 91%
“…High heritability was reported in sweet corn for the number of kernel rows and the ear length which makes selection more efficient (Hallauer et al, 2011;Jawad Asgh & Sadaqat Me, 1999;Ojo et al, 2020). Solomon et al (2012) found that the ear length and the ear diameter are significantly influenced by GCA.…”
Section: Effect On Ear Qualitymentioning
confidence: 99%